WINTER AND DISPERSAL MOVEMENTS OF WILD TURKEYS IN MICHIGAN'S NORTHERN LOWER PENINSULA - Thomas G. Kulowiec; Jonathan B. Haufler (Wildlife Society Bulletin)
Abstract: Movements and mortality factors were monitored for 18 radio‐telemetered wild turkeys (Meleagris gallopavo silvestris) in the Mio‐Fairview region of Oscoda County, Michigan, from March 1983 to March 1984. Spring dispersal from the 389 ha wintering area trap site began by early April. Seventy‐eight percent of the adult birds dispersed early, before 25 April, while 86% of the juveniles did not move off the wintering grounds until after this date. Sixty‐nine percent of the turkeys dispersed to within a 10 km radius of the wintering area, with 50% remaining within 8 km of the area. Five birds (3 adult females, 1 adult male, and 1 juvenile female) made initial movements of greater than 10 km. Movement back toward specific wintering areas began with the first snowfalls in mid‐to late November. Seventy‐three percent of the surviving marked turkeys returned to the area used the previous winter. Wintering areas were located almost exclusively on active farms. Causes of mortality were also investigated and a variety of mortality factors were found to influence the turkey population.